Non-autonomous nonlinear integro-differential equations with infinite delay - Bahuguna, D.; Pandey, D.N.; Ujlayan, A. (Nonlinear analysis, 2009)
In this paper we consider a non-autonomous abstract nonlinear Volterra integro-differential equation with infinite delay in a Banach space. We establish the existence and uniqueness of a strict solution under a certain local Lipschitz condition on the nonlinear map and an integrability condition on the kernel.